Effects of water sources and watering frequency for dairy cattle on water offered and milk production in Kiambu District - Muli, A.N.; Kaitho, R.; Gachuiri, C.K.; Wahome, R.G.; Tanner, J.C. (International Livestock Research Institute, 1998)
Data on water sources, mode of offer, watering frequency, amount of water offered, body weights and milk yield were collected from 21 randomly selected smallholder farms in Kiambu by means of farm visits and questionnaires fortnightly. Most farms (67%) had water on-farm but 76% of them needed labour to deliver the water to the animals. Fifty two percent of the farms practised continuous watering. Water troughs (67%) were mostly used to water dairy cattle.